Effect of magnetic of addition Co0.5Ni0.5Fe2O4 nanoparticles on the microstructure and electric transport properties of YBCO superconductor - Nabilah Sahira, Nor Azman (2017)
In this research, the effect of small amount of Co0.5Ni0.5Fe2O4 magnetic nanoparticles were investigated to improve the microstructure and electric transport properties of YBCO superconductor. Pure YBa2Cu3O7 was synthesized by solid state reaction method and underwent several characterization which were Meissner effect, phase confirmation of YBCO composite was done X-ray Diffractometer (XRD). Then,microstructural analysis is performed using Scanning Electron Microscope (SEM) also critical temperature, Tc was measured by using four point probe method. For Meissner effect, the sample with 0.04 wt% of Co0.5Ni0.5Fe2O4 nanoparticles showed the longest time levitating on the permanent magnet with 20.87 seconds which can be proven that the sample have higher Tc compared to other. Next, the XRD pattern indicated that all the samples were in single orthorhombic crystal structure. The internal microstructure of YBCO showed porosity in grain and size particle decreased when the small amount of nanoparticles was added. Lastly, the Tc cannot be identified through four point probe method due to the result were significantly different with temperature of liquid nitrogen.